Lappaol F, an anticancer agent, inhibits YAP via transcriptional and post-translational regulation - Xiao Li; Yi-Ying Lin; Jia-Yi Tan; Kang-Lun Liu; Xiao-Ling Shen; Ying-Jie Hu; Rui-Yi Yang (Taylor & Francis Group, 2021)
Context Lappaol F (LAF), a natural lignan from Arctium lappa Linné (Asteraceae), inhibits tumour cell growth by inducing cell cycle arrest. However, its underlying anticancer mechanism remains unclear. Objective The effects of LAF on the Hippo-Yes-associated protein (YAP) signalling pathway, which plays an important role in cancer progression, were explored in this study. Materials and methods Cervical (HeLa), colorectal (SW480), breast (MDA-MB-231) and prostate (PC3) cancer cell lines were treated with LAF at different concentrations and different durations. BALB/c nude mice bearing colon xenografts were intravenously injected with vehicle, LAF (10 or 20 mg/kg) or paclitaxel (10 mg/kg) for 15 days. The expression and nuclear localisation of YAP were analysed using transcriptome sequencing, quantitative PCR, western blotting and immunofluorescence. Results LAF suppressed the proliferation of HeLa, MDA-MB-231, SW480 and PC3 cells (IC50 values of 41.5, 26.0, 45.3 and 42.9 μmol/L, respectively, at 72 h), and this was accompanied by significant downregulation in the expression of YAP and its downstream target genes at both the mRNA and protein levels. The expression of 14-3-3σ, a protein that causes YAP cytoplasmic retention and degradation, was remarkably increased, resulting in a decrease in YAP nuclear localisation. Knockdown of 14-3-3σ with small interfering RNA partially blocked LAF-induced YAP inhibition and anti-proliferation effects. In colon xenografts, treatment with LAF led to reduced YAP expression, increased tumour cell apoptosis and tumour growth inhibition. Conclusion LAF was shown to be an inhibitor of YAP. It exerts anticancer activity by inhibiting YAP at the transcriptional and post-translational levels.